Developing a framework for sustainable manufacturing of technologies in Africa focusing on Ghana - Donani, Yao-Martin (2014)
This thesis is concerned with developing a framework for the sustainable manufacturing of technologies in Sub-Saharan Africa, focusing on Ghana, for local industry. The interest here is on manufacturing and production technologies.